Titanium alloy plate, titanium alloy coil, and method for producing titanium alloy plate and method for producing titanium alloy coil
Patent Information
- Application Number
- JP2022577903
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-28
- Publication Date
- 2025-02-20
- Estimated Expiration
- 2041-01-28
AI Technical Summary
【0024】 以上説明したように、本開示によれば、高い強度を有するチタン合金板およびチタン合金コイルならびに同チタン合金板の製造方法および同チタン合金コイルの製造方法を提供することが可能となる。
Smart Images

Figure 0007633542000006 
Figure 0007633542000007 
Figure 0007633542000008
Abstract
Description
[Technical field]
[0001] The present disclosure relates to titanium alloy sheets and coils, as well as methods for making titanium alloy sheets and coils. [Background technology]
[0002] Titanium is a lightweight, high-strength, and corrosion-resistant material that can be applied to the aircraft industry from the perspectives of weight reduction and fuel efficiency. Therefore, titanium alloys that meet the characteristics required for each component of an aircraft are being actively developed.
[0003] For example, Patent Document 1 discloses an α+β type titanium alloy wire containing 1.4% or more and less than 2.1% Fe, 4.4% or more and less than 5.5% Al, and the balance being titanium and impurities.
[0004] Patent Document 2 discloses an α+β type titanium alloy bar material containing 0.5% or more and less than 1.4% Fe, 4.4% or more and less than 5.5% Al, the balance being titanium and impurities.
[0005] Patent Document 3 discloses a method for manufacturing a Ti-6Al-4V alloy thin plate by pack rolling, in which one or more plate-shaped core materials are covered with a spacer material and a cover material to form a packed rolled material, and this packed material is rolled to reduce the thickness of the core materials, characterized in that the thickness of the cover material is set so that the ratio of the core material to the pack material is at least 0.25 for the initial thickness of each of the plates.
[0006] Patent Document 4 discloses a method for manufacturing a Ti-6Al-4V alloy thin plate by pack rolling, in which one or more plate-shaped core materials are covered with a spacer material and a cover material to form a packed material, and this packed material is rolled to reduce the thickness of the core material, characterized in that the rolling reduction ratio of the plate thickness before and after reduction of the packed material is 3 or more, and the rolling rate per pass is 15% or more.
[0007] Patent Document 5 discloses a method for producing a titanium alloy sheet, which comprises cold rolling a hot-rolled annealed sheet of a titanium alloy consisting of, by weight, 2.5-3.5% Al, 2.0-3.0% V, the balance being Ti and ordinary impurities, in the same direction as the hot-rolling direction at a total rolling reduction of 67% or more, and then annealing the sheet at a temperature between 650 and 900°C.
[0008] Patent Document 6 discloses a method for producing an α+β type titanium alloy thin plate, which is characterized in that in the manufacturing process of an α+β type titanium alloy cold-rolled plate, intermediate annealing after cold rolling is performed under the following conditions: annealing temperature: temperature range of [β transformation point -25°C] or higher and lower than the β transformation point, annealing time: 0.5 to 4 hours, cooling rate after heating and holding: 0.5 to 5°C / sec, and temperature range for cooling at the above cooling rate: up to 300°C or lower.
[0009] Patent Document 7 discloses an α+β type titanium alloy thin plate that contains at least one fully dissolved β stabilizing element in an Mo equivalent amount of 2.0 to 4.5 mass%, at least one eutectoid β stabilizing element in an Fe equivalent amount of 0.3 to 2.0 mass%, at least one α stabilizing element in an Al equivalent amount of more than 3.0 mass% and not more than 5.5 mass%, with the balance being Ti and unavoidable impurities, and is characterized in that the average grain size of the α phase is 5.0 μm or less, the maximum grain size of the α phase is 10.0 μm or less, the average aspect ratio of the α phase is 2.0 or less, and the maximum aspect ratio of the α phase is 5.0 or less.
[0010] Patent Document 8 describes an α+β type titanium alloy hot-rolled sheet, in which (a) the normal direction (sheet thickness direction) of the hot-rolled sheet is defined as ND, the hot-rolling direction is defined as RD, and the width direction of the hot-rolled sheet is defined as TD, and the normal direction of the (0001) plane of the α phase is defined as the c-axis orientation, the angle that the c-axis orientation makes with ND is defined as θ, and the angle that the plane including the c-axis orientation and ND makes with the plane including ND and TD is defined as Φ, and (b1) θ is 0 degrees or more and 30 degrees or less, and Φ is the angle around the entire circumference (-180 degrees to 180 degrees). (b2) among the (0002) reflection relative intensities of X-rays caused by crystal grains having a θ of 80 degrees or more and less than 100 degrees, and a Φ of ±10 degrees, the strongest intensity is defined as XND; (b3) among the (0002) reflection relative intensities of X-rays caused by crystal grains having a θ of 80 degrees or more and less than 100 degrees, and a Φ of ±10 degrees, the strongest intensity is defined as XTD; and (c) an α+β type titanium alloy sheet having excellent cold rollability and cold handleability is disclosed, characterized in that XTD / XND is 5.0 or more.
[0011] Patent Document 9 describes a high-strength α+β type titanium alloy hot-rolled sheet, which contains, by mass%, 0.8-1.5% Fe, 4.8-5.5% Al, and 0.030% or less N, and contains O and N in a range satisfying Q(%)=0.14-0.38, defined as Q(%)=[O]+2.77·[N], where [O] is the content (mass%) of O and [N] is the content (mass%) of N, with the balance being Ti and unavoidable impurities, and in which: (a) the normal direction of the hot-rolled sheet is ND, the hot-rolling direction is RD, and the width direction of the hot-rolled sheet is TD, the normal direction of the (0001) plane of the α phase is the c-axis orientation, and the c-axis orientation is ND. The present invention discloses a high-strength α+β-type titanium alloy sheet having excellent cold coil (strip) handleability, characterized in that: θ is the angle, φ is the angle between the plane including the c-axis orientation and the ND direction and the plane including ND and TD; (b1) θ is 0 degrees or more and 30 degrees or less, and φ is the angle between the plane including ND and TD, and XND is the strongest intensity among the relative intensities of (0002) reflection of X-rays by crystal grains in which θ is 0 degrees or more and φ is in the full circumference (-180 degrees to 180 degrees); (b2) θ is 80 degrees or more and less than 100 degrees, and φ is the strongest intensity among the relative intensities of (0002) reflection of X-rays by crystal grains in which φ is in the range of ±10 degrees; and (c) XTD / XND is 4.0 or more.
[0012] Patent Document 10 discloses a method for producing an α+β type titanium alloy thin plate, which is characterized in that an α+β type titanium alloy thin plate produced by rolling or forging is subjected to cold rolling at a rolling reduction rate of 20% or more, and then annealed at a temperature of 700°C or more and the β transformation point or less to obtain a plate having a fine equiaxed α structure.
[0013] Non-Patent Document 1 discloses an α+β titanium alloy thin plate having anisotropy in strength in the rolling direction and in the direction perpendicular to the rolling direction.
[0014] Non-Patent Document 2 discloses an α+β titanium alloy thin plate that has been hot-rolled at a temperature higher than the β transformation point to reduce the anisotropy of strength in the rolling direction and in the direction perpendicular to the rolling direction. [Prior art documents] [Patent documents]
[0015] [Patent Document 1] Japanese Patent Publication No. 7-62474 [Patent Document 2] Japanese Patent Publication No. 7-70676 [Patent Document 3] Japanese Patent Publication No. 2001-300603 [Patent Document 4] Japanese Patent Publication No. 2001-300604 [Patent Document 5] Japanese Patent Publication No. 61-147864 [Patent Document 6] Japanese Patent Publication No. 1-127653 [Patent Document 7] Japanese Patent Application Publication No. 2013-227618 [Patent Document 8] International Publication No. 2012 / 115242 [Patent Document 9] International Publication No. 2012 / 115243 [Patent Document 10] Japanese Patent Publication No. 62-33750 [Non-patent literature]
[0016] [Non-Patent Document 1] KOBE STEEL ENGINEERING REPORTS / Vol.59, No.1(2009), P.81~84 [Non-Patent Document 2] KOBE STEEL ENGINEERING REPORTS / Vol.60, No.2(2010), P.50~54 Summary of the Invention [Problem to be solved by the invention]
[0017] However, titanium materials used in aircraft components that require higher strength contain a lot of Al, but because of their large deformation resistance during hot rolling or cold rolling, the allowable load of the rolling machine may be exceeded when manufacturing thin plates. Therefore, it is difficult to manufacture high-strength titanium alloy thin plates using conventional hot rolling or cold rolling methods.
[0018] The present disclosure has been made in consideration of the above problems, and an object of the present disclosure is to provide a titanium alloy plate and a titanium alloy coil having high strength, as well as a method for manufacturing the titanium alloy plate and the titanium alloy coil. [Means for solving the problem]
[0019] The present inventors have found that a titanium alloy sheet has high strength and excellent workability when it contains a predetermined amount of Al and has a texture in which the peak of the degree of accumulation of crystal grains is within a predetermined angle with respect to the width direction of the final rolling in the (0001) pole figure in the sheet thickness direction. Then, they have found a method for producing a titanium alloy sheet by cold rolling that can simultaneously achieve such a chemical composition and texture, and have come to the present disclosure.
[0020] The gist of the present disclosure, which has been completed based on the above findings, is as follows. (1) A titanium alloy plate according to an embodiment of the present disclosure contains, by mass%, Al: more than 4.0% and not more than 6.6%, Fe: 0% or more and not more than 2.3%, V: 0% or more and not more than 4.5%, Si: 0% or more and not more than 0.60%, C: 0% or more and less than 0.080%, N: 0% or more and not more than 0.050%, O: 0% or more and not more than 0.40%, Ni: 0% or more and not more than 0.15%, Cr: 0% or more and not more than 0.25%, and Mn: 0% or more and not more than 0.25%, with the remainder being Ti and and impurities, the area ratio of the α phase is 80% or more, the area ratio of the α phase having a circle equivalent diameter of 1 μm or more is more than 53%, in the (0001) pole figure from the thickness direction, the inverse pole figure using the spherical harmonic function method of electron backscatter diffraction has an expansion index of 16, the angle between the direction showing the peak of the concentration calculated by texture analysis when the Gaussian half width is 5° and the thickness direction is 65° or less, and the average thickness is 2.5 mm or less. (2) The titanium alloy plate described in (1) above has a microstructure consisting of an equiaxed structure having an aspect ratio of 3.0 or less and a band structure having an aspect ratio of more than 3.0 and extending in the longitudinal direction, and the average crystal grain size of the equiaxed structure is 0.5 and the area ratio of the band structure to the area of the microstructure may be 10.0% or less. (3) The titanium alloy plate according to (1) or (2) above may contain, by mass%, either Fe: 0.5% or more and 2.3% or less, or V: 2.5% or more and 4.5% or less. (4) The titanium alloy plate according to any one of the above (1) to (3) may contain, in mass%, one or more selected from the group consisting of Ni: less than 0.15%, Cr: less than 0.25%, and Mn: less than 0.25%, instead of a part of the Fe or V. (5) The titanium alloy plate according to any one of the above (1) to (4) may have a smaller one of a 0.2% yield strength in the longitudinal direction at 25°C and a 0.2% yield strength in the width direction at 25°C of 700 MPa or more and 1200 MPa or less. (6) In the titanium alloy plate according to any one of the above (1) to (5), in a (0001) pole figure from the plate thickness direction, the angle between the direction showing the peak of the degree of accumulation calculated by texture analysis when the expansion index is 16 and the Gaussian half-width is 5° and the width direction is 10° or less, and the ratio of the 0.2% proof stress in the width direction to the 0.2% proof stress in the longitudinal direction may be 1.05 or more and 1.18 or less. (7) In the titanium alloy plate according to any one of the above (1) to (5), in the (0001) pole figure from the plate thickness direction, the angle between the direction showing the peak of the degree of accumulation calculated by texture analysis when the expansion index is 16 and the Gaussian half width is 5° and the plate thickness direction is 35° or less, and the ratio of the 0.2% proof stress in the width direction to the 0.2% proof stress in the longitudinal direction may be 0.85 or more and 1.10 or less. (8) The titanium alloy plate according to any one of the above (1) to (7) may have a thickness dimensional accuracy of 5.0% or less with respect to the average thickness.
[0021] (9) A titanium alloy coil according to another embodiment of the present disclosure contains, by mass%, Al: more than 4.0% and not more than 6.6%, Fe: 0% or more and not more than 2.3%, V: 0% or more and not more than 4.5%, Si: 0% or more and not more than 0.60%, C: 0% or more and less than 0.080%, N: 0% or more and not more than 0.050%, O: 0% or more and not more than 0.40%, Ni: 0% or more and less than 0.15%, Cr: 0% or more and less than 0.25%, and Mn: 0% or more and less than 0.25%, with the balance being Ti. and impurities, the area ratio of the α phase is 80% or more, the area ratio of the α phase having a circle equivalent diameter of 1 μm or more is more than 53%, in the (0001) pole figure from the thickness direction, the inverse pole figure using the spherical harmonic function method of electron backscatter diffraction has an expansion index of 16, the angle between the direction showing the peak of the concentration calculated by texture analysis when the Gaussian half width is 5° and the thickness direction is 65° or less, and the average thickness is 2.5 mm or less.
[0022] (10) A method for producing a titanium alloy plate according to still another embodiment of the present disclosure is a method for producing a titanium alloy plate according to any one of the above (1) to (8), comprising the steps of: Al: more than 4.0% and 6.6% or less; Fe: 0% or more and 2.3% or less; V: 0% or more and 4.5% or less; Si: 0% or more and 0.60% or less; C: 0% or more and less than 0.080%; N: 0% or more and 0.050% or less; O: 0% or more and 0.40% or less; Ni: 0% or more and 0 The method includes a cold rolling process in which one or more cold rolling passes are performed in the longitudinal direction of a titanium material containing Ti: less than 0.15%, Cr: 0% or more but less than 0.25%, and Mn: 0% or more but less than 0.25%, with the remainder being Ti and impurities, and a final annealing process in which the titanium material is annealed after the last cold rolling pass, wherein the rolling reduction rate per cold rolling pass in the cold rolling process is more than 30% and the total rolling reduction rate is 60% or more. (11) In the method for producing a titanium alloy plate described in (10) above, when a plurality of cold rolling passes are performed, the cold rolling step includes an intermediate annealing step of annealing the titanium material between the plurality of cold rolling passes, and the annealing conditions of the intermediate annealing step and the final annealing step are an annealing temperature of 600° C. or more (T β -50)°C or lower, and the annealing temperature T (°C) and the holding time t (seconds) at the annealing temperature may satisfy the following formula (1): 22000≦(T+273.15)×(Log 10 (t)+20)≦27000…Formula (1) Here, T β is the β transformation point (℃). (12) A method for producing a titanium alloy plate according to still another embodiment of the present disclosure is a method for producing a titanium alloy plate according to any one of the above (1) to (8), comprising the steps of: Al: more than 4.0% and 6.6% or less; Fe: 0% or more and 2.3% or less; V: 0% or more and 4.5% or less; Si: 0% or more and 0.60% or less; C: 0% or more and less than 0.080%; N: 0% or more and 0.050% or less; O: 0% or more and 0.40% or less; Ni: 0% or more and less than 0.15%; Cr: 0% or more and less than 0.25%, and Mn: 0% or more and less than 0.25%, with the balance being Ti and impurities; and a final annealing process for annealing the titanium material after the cold cross rolling process, wherein a total rolling reduction ratio in the cold cross rolling process is 60% or more, and a cross rolling ratio, which is the ratio of the rolling reduction ratio in the longitudinal direction to the rolling reduction ratio in the width direction, is 0.05 or more and 20.00 or less. (13) In the method for producing a titanium alloy plate according to the above (12), when a plurality of cold rolling passes are performed, the cold rolling process or the cold cross rolling process includes an intermediate annealing process for annealing the titanium material between the plurality of cold rolling passes, and the annealing conditions of the intermediate annealing process and the final annealing process include an annealing temperature of 600° C. or more (T β -50)°C or lower, and the annealing temperature T (°C) and the holding time t (seconds) at the annealing temperature may satisfy the following formula (1): 22000≦(T+273.15)×(Log 10 (t)+20)≦27000…Formula (1) Here, T β is the β transformation point (℃).
[0023] (14) A method for producing a titanium alloy coil according to yet another embodiment of the present disclosure is a method for producing a titanium alloy coil according to the above (9), comprising the steps of: Al: more than 4.0% and not more than 6.6%, Fe: 0% or more and not more than 2.3%, V: 0% or more and not more than 4.5%, Si: 0% or more and not more than 0.60%, C: 0% or more and less than 0.080%, N: 0% or more and not more than 0.050%, O: 0% or more and not more than 0.40%, Ni: 0% or more and not more than 0.15%. the cold rolling process comprising one or more cold rolling passes in the longitudinal direction of a titanium material containing less than 0.25%, Cr: 0% or more and less than 0.25%, and Mn: 0% or more and less than 0.25%, with the balance being Ti and impurities; and a final annealing process in which the titanium material is annealed after the last cold rolling pass, wherein the rolling reduction rate per cold rolling pass in the cold rolling process is more than 30%, and the total rolling reduction rate is 60% or more. Effect of the Invention
[0024] As described above, according to the present disclosure, it is possible to provide a titanium alloy plate and a titanium alloy coil having high strength, as well as a method for manufacturing the titanium alloy plate and the titanium alloy coil. [Brief description of the drawings]
[0025] [Figure 1] FIG. 2 is an example of a (0001) pole figure from the plate thickness direction (ND) of a titanium alloy plate according to an embodiment of the present disclosure. [Diagram 2] 11 is a diagram for explaining an angle formed between a direction showing a peak of integration density and the width direction. FIG. [Diagram 3] FIG. 2 is a diagram showing an example of an optical microscope photograph of the titanium alloy plate according to the embodiment. [Figure 4] 1 is an optical microscope photograph showing an example of a band structure. [Diagram 5] FIG. 2 is a schematic diagram for explaining a method for measuring an average plate thickness. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] Hereinafter, preferred embodiments of the present disclosure will be described in detail with reference to the drawings. The description will be made in the following order. 1. Titanium alloy plate 2. Manufacturing method of titanium alloy plate
[0027] <1. Titanium alloy plate> First, the titanium alloy plate according to the present embodiment will be described with reference to Figs. 1 to 5. Fig. 1 is an example of a (0001) pole figure from the plate thickness direction (ND) of the titanium alloy plate according to the present embodiment. Fig. 2 is a diagram for explaining the angle between the direction showing the peak of the integration degree and the width direction. The (0001) pole figure from the plate thickness direction (ND) in Fig. 2 is the same as Fig. 1. Fig. 3 is a diagram showing an example of an optical microscope photograph of the titanium alloy plate according to the present embodiment. Fig. 4 is an optical microscope photograph showing an example of a band structure. Fig. 5 is a schematic diagram for explaining a method for measuring the average plate thickness. The titanium alloy plate according to the present embodiment can be manufactured by a method including a cold rolling process, as will be described in detail later.
[0028] (1.1. Chemical composition) First, the chemical components contained in the titanium alloy plate according to this embodiment will be described. The titanium alloy plate according to this embodiment contains, in mass%, Al: more than 4.0% and 6.6% or less, Fe: 0% or more and 2.3% or less, V: 0% or more and 4.5% or less, Si: 0% or more and 0.60% or less, C: 0% or more and less than 0.080%, N: 0% or more and 0.050% or less, O: 0% or more and 0.40% or less, Ni: 0% or more and less than 0.15%, Cr: 0% or more and less than 0.25%, and Mn: 0% or more and less than 0.25%, with the balance being Ti and impurities. In the following description of the chemical components, unless otherwise specified, the notation "%" shall represent "mass%".
[0029] Al is an α-phase stabilizing element and has high solid solution strengthening ability. When the Al content increases, the tensile strength at room temperature increases. If the Al content is more than 4.0%, high tensile strength can be obtained. Furthermore, the hot-rolled sheet before cold rolling can maintain high cold rolling properties. The Al content is preferably 4.5% or more, more preferably 4.6% or more. On the other hand, if the Al content is more than 6.6%, the cold rolling properties of the hot-rolled sheet before cold rolling are significantly reduced, and regions in which Al is excessively dissolved due to solidification segregation or the like are locally generated, and Al is ordered. This region in which Al is ordered reduces the impact toughness of the titanium alloy sheet. Therefore, the Al content is 6.6% or less, preferably 6.5% or less, more preferably 6.4% or less.
[0030] Fe is a β-phase stabilizing element. Since Fe is an element with high solid solution strengthening ability, increasing the Fe content increases the tensile strength at room temperature. In addition, since the β phase has high workability compared to the α phase, increasing the Fe content improves the workability of the titanium alloy plate and makes it possible to improve the dimensional accuracy. Since Fe is not essential for the titanium alloy plate, the lower limit of its content is 0%. However, in order to obtain the desired tensile strength while maintaining the β phase with good workability at room temperature, the Fe content is preferably 0.5% or more. The Fe content is more preferably 0.7% or more. On the other hand, since Fe is an element that is very prone to solidification segregation, when Fe is contained in excess, Fe segregates locally, and the characteristics may vary between the part where Fe is segregated and the part where it is not segregated. In addition, when Fe is contained in excess in the titanium alloy plate, the fatigue strength may decrease. Therefore, the Fe content is preferably 2.3% or less. The Fe content is more preferably 2.1% or less, and more preferably 2.0% or less. Fe is less expensive than β-phase stabilizing elements such as V or Si.
[0031] The Fe that may be contained in the titanium alloy plate according to this embodiment may be replaced with V. V is a completely dissolved β-phase stabilizing element and has a solid solution strengthening ability. Since V is not essential in the titanium alloy plate, the lower limit of its content is 0%. However, in order to obtain the same solid solution strengthening ability as Fe described above, the V content is preferably 2.5% or more. The V content is more preferably 3.0% or more. Although the cost increases when Fe is replaced with V, V is less likely to segregate than Fe, so the variation in characteristics due to segregation is suppressed. As a result, it becomes easier to obtain stable characteristics in the longitudinal and width directions of the titanium alloy plate. In order to suppress the variation in characteristics due to the segregation of V, the V content is preferably 4.5% or less. As described above, V is less likely to segregate than Fe, so V is preferably contained in the titanium material when manufacturing a large ingot.
[0032] Although Si is a β-phase stabilizing element, it also dissolves in the α-phase and exhibits high solid-solution strengthening ability. As described above, Fe may segregate when contained in a titanium alloy plate at more than 2.3%, so Si may be added as necessary to increase the strength of the titanium alloy plate. In addition, Si has an opposite tendency to segregate to O described below, and is less likely to solidify and segregate than O. Therefore, by adding an appropriate amount of Si and O to the titanium alloy plate, it is expected that high fatigue strength and tensile strength can be achieved at the same time. On the other hand, if the Si content is high, an intermetallic compound of Si called silicide is formed, and the fatigue strength of the titanium alloy plate may decrease. If the Si content is 0.60% or less, the generation of coarse silicide is suppressed, and the decrease in fatigue strength is suppressed. Therefore, the Si content is preferably 0.60% or less. The Si content is more preferably 0.50% or less, and even more preferably 0.40% or less. Since Si is not essential in the titanium alloy plate, the lower limit of the Si content is 0%, but the Si content may be, for example, 0.10% or more.
[0033] If a large amount of C is contained in the titanium alloy plate, it may reduce the ductility or workability of the titanium alloy plate. Therefore, the C content is preferably less than 0.080%. Since C is not essential in the titanium alloy plate, the lower limit of the C content is 0%. Note that C is an unavoidable contaminant, and the actual content is usually 0.0001% or more. The C content is more preferably 0.060% or less.
[0034] Like C, when N is contained in a large amount in titanium alloy plate, it may reduce the ductility or workability of the titanium alloy plate. Therefore, the upper limit of N content is preferably 0.050%. Since N is not essential in titanium alloy plate, the lower limit of its content is 0%. Note that N is an unavoidable contaminant, and its actual content is usually 0.0001% or more. The N content is more preferably 0.04% or less.
[0035] Similarly to C, when O is contained in a large amount in titanium alloy plate, it may reduce the ductility or workability of titanium alloy plate. Therefore, the upper limit of O content is preferably 0.40%, more preferably 0.38%, and even more preferably 0.35%. Since O is not essential in titanium alloy plate, the lower limit of its content is 0%. Note that O is an unavoidable mixture, and its actual content is usually 0.01% or more.
[0036] Ni, like Fe or V, is an element that improves tensile strength and workability. However, if the Ni content is 0.15% or more, the equilibrium phase of the intermetallic compound Ti2Ni is generated, and the fatigue strength and room temperature ductility of the titanium alloy plate may deteriorate. Therefore, the Ni content is preferably less than 0.15%. The Ni content is more preferably 0.14% or less, 0.12% or less, and further preferably 0.11% or less. Since Ni is not essential in the titanium alloy plate, the lower limit of the content is 0%, but the Ni content may be, for example, 0.01% or more.
[0037] Cr is an element that improves tensile strength and workability, similar to Fe or V. However, if the Cr content is 0.25% or more, the equilibrium phase of the intermetallic compound TiCr2 is generated, and the fatigue strength and room temperature ductility of the titanium alloy sheet may deteriorate. Therefore, the Cr content is preferably less than 0.25%. The Cr content is more preferably 0.24% or less, 0.21% or less. Since Cr is not essential in the titanium alloy sheet, the lower limit of the Cr content is 0%, but the Cr content may be, for example, 0.01% or more.
[0038] Mn, like Fe or V, is an element that improves tensile strength and workability. However, if the Mn content is 0.25% or more, an equilibrium phase of intermetallic compound TiMn is generated, and the fatigue strength and room temperature ductility of the titanium alloy plate may deteriorate. Therefore, the Mn content is preferably less than 0.25%. The Mn content is more preferably 0.24% or less, and even more preferably 0.20% or less. Since Mn is not essential in the titanium alloy plate, the lower limit of its content is 0%, but the Mn content may be, for example, 0.01% or more.
[0039] Considering the effects of the above-mentioned chemical components, the titanium alloy plate according to this embodiment preferably contains, as optional elements, Fe: 0.5-2.3% or V: 2.5-4.5%, Si: 0-0.60%, and further contains C: less than 0.080%, N: 0.050% or less, and O: 0.40% or less.
[0040] In addition, considering the effects of the above-mentioned chemical components, when the titanium alloy plate according to this embodiment contains either Fe: 0.5-2.3% or V: 2.5-4.5%, it is preferable to contain one or more selected from the group consisting of Ni: less than 0.15%, Cr: less than 0.25%, and Mn: less than 0.25% instead of a part of Fe or V.
[0041] In the case where the titanium alloy plate according to the present embodiment contains Fe, when it contains one or more selected from the group consisting of Ni: less than 0.15%, Cr: less than 0.25%, and Mn: less than 0.25%, the total amount of Fe, Ni, Cr, and Mn is preferably 0.5% or more and 2.3% or less. When the total amount of Fe, Ni, Cr, and Mn is 0.5% or more, high tensile strength is obtained. In addition, when the total amount of Fe, Ni, Cr, and Mn is 0.5% or more, the β phase with good workability is maintained at room temperature, improving the workability of the titanium alloy plate, so that it is possible to improve the dimensional accuracy. In addition, when the total amount of Fe, Ni, Cr, and Mn is 2.3% or less, the segregation of these elements is suppressed, and it is possible to suppress the variation in properties of the titanium alloy plate.
[0042] In addition, when the titanium alloy plate according to the present embodiment contains V, when it contains one or more selected from the group consisting of Ni: less than 0.15%, Cr: less than 0.25%, and Mn: less than 0.25%, the total amount of V, Ni, Cr, and Mn is preferably 2.5% or more and 4.5% or less. When the total amount of V, Ni, Cr, and Mn is 2.5% or more, high tensile strength is obtained. In addition, when the total amount of V, Ni, Cr, and Mn is 2.5% or more, the β phase with good workability is maintained at room temperature, improving the workability of the titanium alloy plate, so that it is possible to improve the dimensional accuracy. In addition, when the total amount of Fe, Ni, Cr, and Mn is 4.5% or less, the segregation of these elements is suppressed, and it is possible to suppress the variation in properties of the titanium alloy plate.
[0043] The balance of the chemical composition of the titanium alloy plate according to this embodiment may be Ti and impurities. The impurities are, for example, H, Cl, Na, Mg, Ca, B mixed in during the refining process, and Zr, Sn, Mo, Nb, Ta, and Cu mixed in from scrap. The total amount of impurities is 0.5% or less, which is not a problem. The H content is 150 ppm or less. There is a concern that B may become coarse precipitates in the ingot. Therefore, even if it is contained as an impurity, it is preferable to suppress the B content as much as possible. In the titanium alloy plate according to this embodiment, the B content is preferably 0.01% or less.
[0044] In addition, when the titanium alloy plate according to this embodiment contains 0.5 to 2.3% Fe, the amount of V contained in the titanium alloy plate may be considered as an impurity, and when the titanium alloy plate according to this embodiment contains 2.5 to 4.5% V, the amount of Fe contained in the titanium alloy plate may be considered as an impurity.
[0045] In addition, as long as the titanium alloy plate according to this embodiment has high strength and excellent dimensional accuracy, it goes without saying that it can contain various elements instead of Ti.Similarly, as long as the titanium alloy plate has high strength and excellent dimensional accuracy, it can contain the elements exemplified as impurities in an amount greater than the amount considered as impurities.
[0046] As described above, the titanium alloy plate according to this embodiment can have the above-mentioned chemical composition. More specifically, the chemical composition of the titanium alloy plate according to this embodiment can be, for example, Ti-6Al-4V, Ti-6Al-4V ELI, Ti-5Al-1Fe.
[0047] (1.2. Texture and Microstructure) Next, the texture and microstructure of the titanium alloy plate according to this embodiment will be described.
[0048] [Collective tissue] The titanium alloy plate according to the present embodiment has a texture in which the angle between the direction showing the peak of the degree of accumulation calculated by texture analysis in the case where the expansion index is 16 and the Gaussian half-width is 5° in the inverse pole figure using the spherical harmonic function method of the electron backscatter diffraction (EBSD) method in the thickness direction is 65° or less. When titanium alloys are generally hot-rolled in one direction at high speed at a temperature in the β region or the α+β high temperature region where the β phase ratio is high, a texture (T-texture) in which the c-axis of the hexagonal close-packed (hcp) structure is oriented in the width direction perpendicular to the longitudinal direction on the rolled surface is formed due to the variant selection rule during the phase transformation from β phase to α phase. In a texture in which the c-axis of the hcp is oriented in the width direction, large anisotropy occurs in the tensile properties in the width direction and the longitudinal direction. If there is large anisotropy in the tensile properties in the width direction and the longitudinal direction, problems may occur during processing. The direction showing the peak of the density calculated by the texture analysis (expansion index = 16, Gaussian half-width = 5 °) of the inverse pole figure using the spherical harmonic function method of the EBSD method corresponds to the direction in which the c-axis of the hcp is most oriented. In the (0001) pole figure from the thickness direction of the titanium alloy plate according to the present embodiment, the angle between the direction in which the c-axis of the hcp is most oriented (the direction showing the peak of the density) and the thickness direction is 65 ° or less, so that it is possible to reduce anisotropy, ensure high workability, and improve dimensional accuracy. In the (0001) pole figure from the thickness direction, the angle between the direction in which the c-axis of the hcp is most oriented and the thickness direction is preferably 60 ° or less, more preferably 55 ° or less, and even more preferably 35 ° or less. The lower limit of the angle between the direction in which the c-axis of the hcp is most oriented and the thickness direction is not particularly limited, but is 0 ° or more. When a titanium alloy sheet is produced by unidirectional rolling, the lower limit of the angle between the direction in which the hcp c-axis is most oriented and the sheet thickness direction is 20° or more.
[0049] In addition, when cold rolling is performed in one direction, the angle between the direction showing the peak of the density and the sheet thickness direction may become a texture (Split-TD texture) in which the c-axis of the hcp axis is inclined toward the width direction (TD). The Split-TD texture has excellent formability, particularly excellent bendability. Therefore, the angle between the direction showing the peak of the density and the sheet thickness direction is preferably 20° or more and 65° or less, which is a Split-TD texture.
[0050] The (0001) pole figure can be obtained by chemically polishing the observation surface of a titanium alloy plate sample and analyzing the crystal orientation using EBSD. Specifically, the titanium alloy plate is cut in the thickness direction along the longitudinal direction at the center position of the width direction (TD), and a cross section (L cross section) is chemically polished. A (0001) pole figure can be created by performing crystal orientation analysis using the EBSD method on 2 to 10 points at intervals of 1 to 2 μm in an area of (total plate thickness) × 2 mm on the cross section. The peak position of the concentration of a specific orientation in the (0001) pole figure can be determined by using the data in the OIM Analysis software provided by TSL Solutions. TM The calculation is performed using software (Ver.8.1.0) and texture analysis of the inverse pole figure using the spherical harmonic function method. The position with the highest contour is the peak position of the concentration, and the value with the highest concentration among the peak positions is the maximum concentration. The concentration of a specific orientation in the (0001) pole figure indicates how many times the frequency of crystal grains with that orientation is compared to a structure with a completely random orientation distribution (concentration of 1). In the above, the L-section at the center position in the width direction is used as the observation surface, but since the crystal orientation of titanium alloy plate is uniformly distributed in the width direction, the L-section at any position in the plate width may be used as the observation surface.
[0051] FIG. 1 shows an example of a (0001) pole figure from the plate thickness direction (ND) of the titanium alloy plate according to this embodiment. In FIG. 1, the poles of each detected crystal orientation are accumulated according to the inclination to the final rolling direction (RD) and the final rolling width direction (TD), and the (0001) pole figure shows the contour line of accumulation. The part where the contour line is highest in the figure is the peak P1 of the crystal grain. Therefore, in this embodiment, the angle between the direction showing the peak P1 of the crystal grain and ND is 65° or less. Usually, the maximum accumulation degree is the accumulation degree of the peak P1 of the crystal grain.
[0052] In addition, in the titanium alloy plate according to the present embodiment, in the (0001) pole figure from the plate thickness direction, the angle between the direction showing the peak of the density calculated by texture analysis when the expansion index is 16 and the Gaussian half-width is 5° in the inverse pole figure using the spherical harmonic function method of the electron backscattering diffraction method and the width direction may be 10° or less. The angle between the direction showing the peak of the density and the width direction is the angle θ2 between the direction from the center of the (0001) pole figure from the plate thickness direction to the position showing the peak of the density and the width direction (TD), as shown in FIG. The angle is preferably 5° or less, more preferably 3° or less, from the viewpoint of manufacturing and the observation method of the structure. In addition, in the (0001) pole figure of the titanium alloy plate according to this embodiment, in the inverse pole figure using the spherical harmonic function method of the electron backscatter diffraction method, the angle between the direction showing the peak of the accumulation degree calculated by texture analysis when the expansion index is 16 and the Gaussian half-width is 5° and the plate thickness direction may be 35° or less.
[0053] [Microstructure] The titanium alloy plate according to the present embodiment has an α-phase area ratio of 80% or more. The titanium alloy plate according to the present embodiment contains a large amount of α-stabilizing elements to increase strength. Therefore, if the amount of β-stabilizing elements added is further increased, it becomes impossible to manufacture the titanium alloy plate by cold rolling due to excessive strength. Therefore, the titanium alloy plate according to the present embodiment has an α-phase area ratio of 80% or more. The α-phase area ratio may be, for example, 82% or more. The upper limit of the α-phase area ratio is not particularly limited, and the α-phase area ratio may be, for example, 100% or less or 98% or less. The structure of the titanium alloy plate according to the present embodiment is composed of an α-phase and a remaining structure, and the remaining structure includes a β-phase, TiFe, Ti3Al, and silicide.
[0054] In the titanium alloy plate according to the present embodiment, the area ratio of the α phase having an equivalent circle diameter of 1 μm or more is more than 53%. If the area ratio of 1 μm or less is high, the ductility at room temperature may be poor, so the area ratio of the α phase having an equivalent circle diameter of 1 μm or more is more than 53%. The area ratio of the α phase having an equivalent circle diameter of 1 μm or more may be 55% or more, or may be 60% or more. The upper limit of the area ratio of the α phase having an equivalent circle diameter of 1 μm or more is not particularly limited, and the area ratio of the α phase having an equivalent circle diameter of 1 μm or more may be, for example, 98% or less. The microstructure of the titanium alloy plate according to the present embodiment is, for example, as shown in FIG. 3. The upper limit of the equivalent circle diameter of the α phase is not particularly limited, and the equivalent circle diameter of the α phase is, for example, 20 μm or less.
[0055] The area ratio of the α phase and the area ratio of the α phase with a circle equivalent diameter of 1 μm or more are measured by the following method. A cross section (L cross section) of a titanium alloy plate cut in the plate thickness direction along the longitudinal direction at the center position in the width direction (TD) is chemically polished, and a crystal orientation analysis is performed by the EBSD method on an area of (total plate thickness) × 200 μm of the cross section, for about 2 to 5 fields of view at a step of 1 to 5 μm. The α phase is identified by this crystal orientation analysis by EBSD. The area ratio of the α phase is the area ratio of the α phase. In addition, the circle equivalent diameter (area A = π × (grain size D / 2) 2) of the α phase observed in the above field of view is calculated, and the total area of the α phase with a circle equivalent diameter of 1 μm or more with respect to the area of the above region is the area ratio of the α phase with a circle equivalent diameter of 1 μm or more. The crystal grains of the α phase with a circle equivalent diameter of 1 μm or more are to include the band structure described later. In the above, the area ratio of the α phase and the area ratio of the α phase having a circle equivalent diameter of 1 μm or more are measured based on an L cross section at the center position in the width direction. However, since the α phase is uniformly distributed in the width direction, the area ratio of the α phase and the area ratio of the α phase having a circle equivalent diameter of 1 μm or more may also be measured based on an L cross section at any sheet width position.
[0056] The titanium alloy plate according to the present embodiment has a microstructure consisting of an equiaxed structure with an aspect ratio of 3.0 or less and a band structure with an aspect ratio of more than 3.0 and extending in the longitudinal direction, and the average crystal grain size of the equiaxed structure is preferably 0.1 μm or more and 20.0 μm or less, and the area ratio of the band structure to the area of the microstructure is preferably 10.0% or less. Each structure will be described below.
[0057] When titanium alloys are hot-rolled at temperatures in the α+β region or β region, a structure called a "band structure" may be formed as shown in FIG. 4. The band structure referred to here is, for example, a structure elongated in the longitudinal direction as shown in FIG. 4. Specifically, it refers to crystal grains whose aspect ratio represented by the long axis / short axis of the crystal grain exceeds 3.0. The titanium alloy plate according to this embodiment may have a band structure elongated in the longitudinal direction. If the band structure is formed, it may cause anisotropy of strength or defects during forming. Therefore, it is better to have as few band structures as possible. The area ratio of the band structure to the area of the microstructure is preferably 10.0% or less. The area ratio of the band structure is more preferably 8.0% or less. On the other hand, since it is better to have no band structure, the lower limit is 0%.
[0058] The aspect ratio and the area ratio of the band structure can be calculated as follows. A cross section (L cross section) of a titanium alloy plate cut in the thickness direction along the longitudinal direction at the center position in the width direction (TD) is chemically polished, and a crystal orientation analysis is performed by the EBSD method on an area of (total plate thickness) × 200 μm of the cross section, with steps of 1 to 5 μm, for about 2 to 5 fields of view. From the results of this EBSD crystal orientation analysis, the aspect ratio is calculated for each crystal grain. Then, the area ratio of crystal grains with an aspect of more than 3.0 is calculated. In the above, the aspect ratio and the area ratio of the band structure are calculated based on the L cross section at the center position in the width direction, but since the band structure is uniformly distributed in the width direction, the aspect ratio and the area ratio of the band structure may be calculated based on the L cross section at any plate width position.
[0059] The remaining part of the microstructure other than the band structure is preferably an equiaxed structure formed by recrystallization. The titanium alloy plate preferably has an equiaxed structure from the viewpoint of formability, and in particular, the titanium alloy plate is preferably fine-grained since it may be formed by utilizing superplasticity. From the viewpoint of formability and superplasticity, the average crystal grain size of the equiaxed structure is preferably 20.0 μm or less. The average crystal grain size of the equiaxed structure is more preferably 15.0 μm or less, even more preferably 10.0 μm or less, and even more preferably 8.0 μm or less. On the other hand, if the average crystal grain size of the equiaxed structure is less than 0.5 μm, the strength may become too large due to the effect of fine grains, and the ductility may be significantly reduced. As a result, the workability may be reduced, especially in the cold (room temperature). Therefore, the average crystal grain size of the equiaxed structure is preferably 0.5 μm or more. The average crystal grain size of the equiaxed structure is more preferably 1.0 μm or more. In addition, the equiaxed structure and band structure are more than 80% α phase, and β phase exists between the α phases.
[0060] The presence or absence of recrystallization can be determined by measuring the aspect ratio of the crystal grain (ratio of long axis to short axis). If the aspect ratio is 3.0 or less, the crystal grain can be determined to be a recrystallized grain. The lower limit of the aspect ratio of an equiaxed structure is 1.0.
[0061] The average grain size of the equiaxed structure can be calculated as follows: The grain area of the equiaxed structure measured by EBSD is used to calculate the circle equivalent grain size (area A = π × (grain size D / 2) 2 ) is calculated, and the average value based on the number is regarded as the average grain size of the equiaxed structure.
[0062] (1.3. 0.2% proof stress) The smaller of the 0.2% proof stress in the longitudinal direction or the 0.2% proof stress in the width direction at 25°C of the titanium alloy plate according to this embodiment is preferably 700MPa or more. Hereinafter, the smaller of the 0.2% proof stress in the longitudinal direction or the 0.2% proof stress in the width direction is simply referred to as 0.2% proof stress. In the aircraft field and the like, a tensile strength close to the tensile strength at 25°C of Ti-6Al-4V, which is a general-purpose α+β type titanium alloy, is often required. If the 0.2% proof stress at 25°C of the titanium alloy plate is 700MPa or more, it can be used in applications requiring high strength. The 0.2% proof stress at 25°C of the titanium alloy plate is more preferably 730MPa or more. On the other hand, if the strength is too high, the strength of the hot-rolled plate before cold rolling is also high, making it difficult to cold-roll the hot-rolled plate, and the number of cold-rolling passes may increase, resulting in increased costs. Also, if the strength is too high, the notch sensitivity increases, and the plate may break. Therefore, the 0.2% proof stress of the titanium alloy plate at 25 ° C is preferably 1200 MPa or less. The 0.2% proof stress of the titanium alloy plate at 25 ° C is more preferably 1150 MPa or less. Furthermore, if the 0.2% proof stress of the titanium alloy plate at 25 ° C is 1000 MPa or less, the cracking during rolling is further suppressed, so the 0.2% proof stress of the titanium alloy plate at 25 ° C is more preferably 1100 MPa or less. The 0.2% proof stress can be measured by a method conforming to JIS Z2241:2011. That is, the 0.2% proof stress in the longitudinal direction and the 0.2% proof stress in the transverse direction can be measured by a method conforming to JIS Z2241:2011. The longitudinal direction referred to here is the final rolling direction. For those skilled in the art, it is easy to identify the final rolling direction, and the final rolling direction is clear.
[0063] (1.4. Anisotropy) In the titanium alloy plate according to the present embodiment, the yield strength ratio σT / σL, which is the ratio of the 0.2% yield strength σT in the width direction at 25°C to the 0.2% yield strength σL in the longitudinal direction at 25°C, is preferably 0.85 or more and 1.18 or less. Since α+β-type titanium has an hcp phase (α phase) as described above, it shows high anisotropy in the hcp direction. As described above, when T-texture is formed, anisotropy becomes large, so that it is sometimes desired to make the anisotropy as small as possible, especially in the aircraft field. Therefore, the yield strength ratio σT / σL is preferably closer to 1.00, but if the yield strength ratio σT / σL is 1.18 or less, better formability can be obtained. The yield strength ratio σT / σL is more preferably 1.16 or less, even more preferably 1.15 or less, and even more preferably 1.14 or less. In the case of cold cross rolling, which performs cold rolling in the longitudinal direction and the width direction, the yield strength ratio σT / σL can be 0.85 or more and 1.10 or less. The yield strength ratio σT / σL of the titanium alloy plate manufactured by cold cross rolling is preferably 0.90 or more, more preferably 0.95 or more. In addition, the yield strength ratio σT / σL of the titanium alloy plate manufactured by cold cross rolling is preferably 1.05 or less. In the case of unidirectional cold rolling in the longitudinal direction, it is difficult to make the yield strength ratio σT / σL less than 1.05, and it can be 1.05 or more. In addition, since it is possible to manufacture a titanium alloy plate with a yield strength ratio σT / σL exceeding 1.18 by unidirectional cold rolling, σT / σL may be more than 1.18.
[0064] (1.5. Average plate thickness) The average thickness of the titanium alloy plate according to the present embodiment is 2.5 mm or less. For example, the average thickness of the titanium alloy plate can be 2.5 mm or less by using a titanium material containing the above chemical components according to the manufacturing method of the titanium alloy plate described later. Since the titanium material with an Al content of more than 4.0% and not more than 6.6% has a large deformation resistance, the allowable load of the rolling machine may be exceeded when manufacturing a thin plate with a general rolling machine. Therefore, it is difficult to manufacture a titanium alloy plate containing the above chemical components and having a thickness of 2.5 mm or less. In addition, when hot rolling is performed without using pack rolling, the temperature drops rapidly as the plate thickness becomes thinner, and the deformation resistance increases. As a result, when hot rolling a high-strength material, the allowable load of the rolling machine may be exceeded, making it difficult to make the average thickness 2.5 mm or less. On the other hand, although there is no particular limit on the lower limit of the average thickness of the titanium alloy plate according to the present embodiment, in a titanium alloy having the above strength, the average thickness is often 0.1 mm or more in reality. Therefore, the average thickness of the titanium alloy plate according to the present embodiment is preferably 0.1 mm or more. The thickness of the titanium alloy plate according to this embodiment is preferably 2.0 mm or less, more preferably 1.5 mm or less. The average thickness of the titanium alloy plate according to this embodiment is more preferably 0.2 mm or more.
[0065] Here, the method for measuring the average thickness will be described with reference to Fig. 5. The thickness of each position is measured at 5 or more positions at intervals of 1 m or more in the longitudinal direction using an X-ray, a micrometer or a vernier caliper, at the center position in the transverse direction (TD) and at positions at a distance of 1 / 4 of the plate width from each end in the transverse direction, and the average of the measured thicknesses is defined as the average thickness.
[0066] (1.6. Plate thickness dimensional accuracy) The thickness dimensional accuracy of the titanium alloy plate according to this embodiment (hereinafter, the thickness dimensional accuracy may be simply referred to as thickness dimensional accuracy) is preferably 5.0% or less with respect to the average plate thickness. In pack rolling, a titanium alloy thin plate is manufactured by hot rolling a titanium material that is laminated and wrapped with a steel material, but since the deformation resistance of the laminated titanium material varies greatly depending on the temperature distribution, it is difficult to manufacture a thin plate with a uniform thickness. However, since the titanium alloy plate according to this embodiment is manufactured through cold rolling as described later, it is a titanium alloy thin plate with excellent thickness dimensional accuracy. The dimensional accuracy of the titanium alloy plate according to this embodiment is more preferably 4.0% or less with respect to the average plate thickness, and even more preferably 2.0% or less with respect to the average plate thickness.
[0067] The thickness dimensional accuracy is measured by the following method. The thickness is measured at five or more locations at intervals of 1 m or more in the longitudinal direction, including the center position in the transverse direction (TD) and positions at a distance of 1 / 4 of the plate width from both ends in the transverse direction, using X-rays, a micrometer, or a vernier caliper. Using the actually measured plate thickness d and the above average plate thickness dave, the maximum value of a' calculated by the following formula (101) is taken as the thickness dimensional accuracy a. a'=(d-dave) / dave×100...Formula (101)
[0068] The titanium alloy plate according to this embodiment has been described above. The titanium alloy plate according to this embodiment has high strength because it has the above-mentioned chemical composition and metal structure. The titanium alloy plate according to this embodiment described above can be manufactured by any method, and can also be manufactured by the manufacturing method of the titanium alloy plate according to this embodiment described below.
[0069] <2. Manufacturing method of titanium alloy plate> The manufacturing method of the titanium alloy plate according to the present embodiment includes a slab manufacturing process for manufacturing a titanium alloy slab, a hot rolling process for hot rolling the titanium alloy slab, a cold rolling process for cold rolling the titanium material after the hot rolling process, and, if necessary, a temper rolling and tensile straightening process for temper rolling or tensile straightening the titanium material after the cold rolling process. Each step of the manufacturing method of the titanium alloy plate according to the present embodiment will be described below. In the cold rolling process, one-way cold rolling is performed in which the titanium material after the hot rolling process is subjected to one or more cold rolling passes only in the longitudinal direction, or cold cross rolling is performed in which the titanium material is subjected to cold rolling passes in the longitudinal direction and the width direction. In the following, as the first manufacturing method, a case in which one-way cold rolling is performed on the titanium material after the hot rolling process in the cold rolling process will be described, and as the second manufacturing method, a case in which cold cross rolling is performed on the titanium material after the hot rolling process will be described.
[0070] [First manufacturing method] (2.1. Slab manufacturing process) In the slab manufacturing process, a titanium alloy slab is manufactured. The manufacturing method of the titanium alloy slab is not particularly limited, and for example, it can be manufactured by the following procedure. First, an ingot is produced from sponge titanium by various melting methods such as a vacuum arc melting method, an electron beam melting method, or a hearth melting method such as a plasma melting method. Next, the obtained ingot is hot forged at a temperature in the α-phase high temperature region, the α + β two-phase region, or the β-phase single-phase region to obtain a titanium alloy slab. Note that the titanium alloy slab may be subjected to pretreatment such as cleaning treatment and cutting as necessary. In addition, when the titanium alloy slab is made into a rectangular shape that can be hot rolled by the hearth melting method, it may be subjected to hot rolling without hot forging or the like. The produced titanium alloy slab contains, by mass%, Al: more than 4.0% and not more than 6.6%, Fe: 0% or more and not more than 2.3%, V: 0% or more and not more than 4.5%, Si: 0% or more and not more than 0.60%, C: 0% or more and less than 0.080%, N: 0% or more and not more than 0.050%, O: 0% or more and not more than 0.40%, Ni: 0% or more and less than 0.15%, Cr: 0% or more and less than 0.25%, and Mn: 0% or more and less than 0.25%.
[0071] (2.2. Hot rolling process) In the hot rolling process, the titanium alloy slab is heated and then hot rolled. For example, the titanium alloy slab is rolled at a temperature above the β transformation point T β After heating to a temperature range of 0.1 °C or more, the slab is rolled so that the total rolling reduction is 80% or more. However, if hot rolling is started at a temperature below the temperature range of the α + β phase, cracks will occur in the titanium alloy slab, or even if no cracks occur, the above-mentioned metal structure will not be obtained. Therefore, in this process, hot rolling is started from the temperature range of the β phase. Also, the finishing temperature immediately after hot rolling is set to the temperature range of the α + β phase, and varies depending on the composition of the titanium alloy slab, but is, for example, (T β -250)℃ or more (T β The reduction ratio may be set to 0.080% or less, and the temperature may be set to 0.050% or less, and the reduction ratio may be set to 0.25% or less. The titanium material after the hot rolling process contains, by mass%, Al: more than 4.0% and 6.6% or less, Fe: 0% or more and 2.3% or less, V: 0% or more and 4.5% or less, Si: 0% or more and less than 0.60%, C: 0% or more and less than 0.080%, N: 0% or more and 0.050% or less, O: 0% or more and 0.40% or less, Ni: 0% or more and less than 0.15%, Cr: 0% or more and less than 0.25%, and Mn: 0% or more and less than 0.25%.
[0072] In this specification, the term "β transformation point" refers to the boundary temperature at which the α phase begins to form when the titanium alloy is cooled from the β single-phase region. The β transformation point can be obtained from a phase diagram. The phase diagram can be obtained, for example, by the CALPHAD (Computer Coupling of Phase Diagrams and Thermochemistry) method. Specifically, the β transformation point can be calculated by obtaining a phase diagram of a titanium alloy using Thermo-Calc, an integrated thermodynamic calculation system from Thermo-Calc Software AB, and a specified database (TI3) by the CALPHAD method.
[0073] In the hot rolling process, the titanium alloy slab can be continuously hot rolled using a known continuous hot rolling facility. When using the continuous hot rolling facility, the titanium alloy slab is hot rolled and then wound by a winder to become a titanium alloy hot rolled coil. Therefore, the titanium material after the hot rolling process includes a plate-shaped titanium material and a coil-shaped titanium material that is longer than the plate-shaped titanium material.
[0074] The titanium material after the hot rolling process may be annealed by a known method, pickled or cut to remove oxide scale, or cleaned, if necessary. For example, the titanium material after the hot rolling process is annealed at a temperature of 650°C to 800°C for 20 minutes to 90 minutes. This allows the non-recrystallized grains of the hot rolled plate to precipitate as fine recrystallized grains, and the crystals in the metal structure of the finally obtained titanium alloy plate can be made more uniform and fine. The annealing may be performed in any of an air atmosphere, an inert atmosphere, and a vacuum atmosphere.
[0075] In addition, in the above-mentioned manufacturing method of titanium alloy plate, the titanium material after the hot rolling process corresponds to the titanium material according to the present disclosure.
[0076] (2.3. Cold rolling process) In this process, the titanium material after the hot rolling process is subjected to one or more cold rolling passes in its longitudinal direction. The rolling ratio per cold rolling pass in the cold rolling process is more than 30%, and the total rolling ratio is 60% or more. The c-axis of the hcp approaches ND by this cold rolling process. However, if the rolling ratio per cold rolling pass and the total rolling ratio are too small, the crystal orientation hardly changes, and the angle between the direction showing the peak of the density and the plate thickness direction does not become 65° or less. In this case, the anisotropy of the titanium alloy plate is not improved. In addition, although the above-mentioned band structure is formed by hot rolling, if the cold rolling ratio per cold rolling pass and the total cold rolling ratio in the cold rolling after the hot rolling are small, the band structure remains in the titanium material without being destroyed. Therefore, the rolling ratio per cold rolling pass in the cold rolling process is more than 30%, and the total rolling ratio is 60% or more. The total rolling ratio is preferably 70% or more.
[0077] In addition, one cold rolling pass here refers to cold rolling that is performed continuously. Specifically, the cold rolling pass refers to cold rolling from after the hot rolling process until the titanium material has a final product thickness, or from after the hot rolling process until before the temper rolling process, if a temper rolling process described later is performed after the hot rolling process. However, if intermediate annealing is performed in the cold rolling process, the cold rolling from the hot rolling process until the intermediate annealing process, and the cold rolling from the intermediate annealing process until the titanium material has a final product thickness, or before the temper rolling process, are each called a cold rolling pass. In addition, if intermediate annealing is performed multiple times, the cold rolling from the previous intermediate annealing process to the subsequent intermediate annealing process is also called a cold rolling pass. In addition, the rolling rate by each cold rolling mill may be any rate as long as the rolling rate per run is more than 30%.
[0078] In this cold rolling process, the titanium material is rolled into a long hot-rolled sheet or a long hot-rolled coil in the rolling direction, which makes it possible to reduce manufacturing costs.
[0079] The cold rolling temperature is preferably 500°C or lower. If the cold rolling temperature is 500°C or lower, high dimensional accuracy can be obtained, and the crystal grains are refined during cold rolling, making it easier to develop superplastic properties. The cold rolling temperature is more preferably 400°C or lower. There is no particular lower limit to the cold rolling temperature, and the cold rolling temperature can be, for example, room temperature or higher. Here, room temperature means 0°C or higher.
[0080] [Intermediate annealing process] In the cold rolling process, when a plurality of cold rolling passes are performed, it is preferable to have an intermediate annealing process in which the titanium material is annealed between the plurality of cold rolling passes. In the intermediate annealing process, the annealing temperature T is 600° C. or higher (T β It is preferable to anneal the intermediate material in the cold rolling process so that the annealing temperature T (°C) and the holding time t (seconds) at the annealing temperature T satisfy the following formula (102). 10 (t)+20) is the Larson-Miller parameter. 22000≦(T+273.15)×(Log 10 (t)+20)≦27000 …Formula (102) Here, T β is the β transformation point (℃).
[0081] [Final annealing process] The final annealing process is a process in which the titanium material after the last cold rolling pass is annealed. The annealing conditions in the final annealing process are not particularly limited, but in order to improve the formability of the titanium alloy sheet, the annealing temperature T is preferably 600°C or higher (T β It is preferable that the annealing temperature T (°C) and the holding time t (seconds) at the annealing temperature T satisfy the above formula (102).
[0082] By carrying out the intermediate annealing process and the final annealing process under the above conditions, the uncrystallized grains are recrystallized and the c-axis of the α phase approaches the ND direction. This makes it possible to reduce the anisotropy of the titanium alloy sheet. In addition, the recrystallization eliminates the excessive band structure in the microstructure. On the other hand, the annealing temperature is higher than the β transformation point T β If the annealing temperature is above 600°C, a phase transformation from the β phase to the α phase occurs, and the α phase thus produced becomes an acicular structure. Even if the annealing temperature is just below the β transformation point, a bimodal structure in which an equiaxed structure and an acicular structure are mixed will result. The acicular structure and bimodal structure can cause internal cracks and edge cracks during cold rolling. Furthermore, the acicular structure or bimodal structure often becomes coarse grains, making it difficult to develop superplastic properties. In the intermediate annealing process and the final annealing process, the annealing temperature T is 600°C or higher (T β By determining the annealing temperature T and the annealing time t so that the annealing temperature T and the annealing time t satisfy the above formula (102), the c-axis of the α phase approaches the ND direction due to recrystallization, and the anisotropy of the titanium alloy sheet can be further reduced, and the band structure in the microstructure can be further reduced. Furthermore, in the intermediate annealing process and the final annealing process, the annealing temperature T is 600°C or higher (T β By determining the annealing temperature T and the annealing time t so that the annealing temperature T and the annealing time t are equal to or lower than −50° C. and satisfy the above formula (102), a fine equiaxed structure is increased, internal cracks and edge cracks during cold rolling are suppressed, and superplastic properties are easily exhibited.
[0083] (2.4. Temper rolling and tensile straightening process) The titanium alloy plate is manufactured through the above-mentioned cold rolling process, and the titanium alloy plate after the cold rolling process is preferably subjected to temper rolling to adjust mechanical properties or tensile straightening to straighten the shape, as necessary. The rolling reduction in temper rolling is preferably 10% or less, and the elongation in tensile straightening is preferably 5% or less. Note that temper rolling and tensile straightening may not be performed if they are not necessary.
[0084] According to the first manufacturing method, in the cold rolling process in which the hot-rolled plate manufactured using the above titanium alloy plate material is cold-rolled once or more in the longitudinal direction, the rolling reduction rate per cold rolling is more than 30% and the total rolling reduction rate is 60% or more, so that a titanium alloy plate is obtained in which the angle between the direction showing the peak of the density calculated by the texture analysis when the expansion index is 16 and the Gaussian half-width is 5° and the plate thickness direction is 65° or less in the (0001) pole figure from the plate thickness direction using the spherical harmonic function method of the EBSD method. In addition, according to the first manufacturing method, the average plate thickness of the titanium alloy plate can be made 2.5mm or less, and the dimensional accuracy of the plate thickness can be made 5.0% or less with respect to the average plate thickness.
[0085] In addition, according to the first manufacturing method, the metal structure of the titanium alloy plate has a microstructure consisting of an equiaxed structure with an aspect ratio of 3.0 or less and a band structure with an aspect ratio of more than 3.0 and extending in the longitudinal direction, the average crystal grain size of the equiaxed structure is 0.1 μm or more and 20.0 μm or less, and the area ratio of the band structure to the area of the microstructure is 10.0% or less. This further reduces the anisotropy of the titanium alloy plate. Furthermore, according to the first manufacturing method, the ratio of the 0.2% proof stress in the width direction to the 0.2% proof stress in the longitudinal direction can be set to 1.05 or more and 1.18 or less.
[0086] Furthermore, according to the first manufacturing method, the crystal grains are refined by cold rolling, which facilitates the development of superplastic properties, and the titanium alloy plate has excellent workability in thin plate forming.
[0087] According to the manufacturing method of the titanium alloy plate according to the present embodiment, since it includes a unidirectional cold rolling process, it is possible to manufacture a long titanium alloy plate and a titanium alloy coil. Therefore, the above manufacturing method can also be said to be a manufacturing method of a titanium alloy coil. Therefore, it goes without saying that the titanium alloy coil manufactured by the above manufacturing method has the same characteristics as the titanium alloy plate of the present disclosure. Specifically, the titanium alloy coil of the present disclosure contains, in mass%, Al: more than 4.0% and 6.6% or less, Fe: 0% or more and 2.3% or less, V: 0% or more and 4.5% or less, Si: 0% or more and 0.60% or less, C: 0% or more and less than 0.080%, N: 0% or more and 0.050% or less, O: 0% or more and 0.40% or less, Ni: 0% or more and less than 0.15%, Cr: 0% or more and less than 0.25%, and Mn: 0% or more and less than 0.25%, with the balance being Ti and and impurities, the area ratio of the α phase is 80% or more, the area ratio of the α phase having a circle equivalent diameter of 1 μm or more is more than 53%, in the (0001) pole figure from the thickness direction, the inverse pole figure using the spherical harmonic function method of electron backscatter diffraction has an expansion index of 16, the angle between the direction showing the peak of the concentration calculated by texture analysis when the Gaussian half width is 5° and the thickness direction is 65° or less, and the average thickness is 2.5 mm or less.
[0088] In addition, when manufacturing a titanium alloy coil, the above-mentioned "longitudinal direction" corresponds to the longitudinal direction of the titanium alloy coil, and the "width direction" corresponds to the direction perpendicular to the longitudinal direction of the rolled surface of the titanium alloy coil. So far, the first manufacturing method has been described.
[0089] [Second manufacturing method] Next, the second manufacturing method will be described. The second manufacturing method differs from the first manufacturing method in the cold rolling process, but the other processes are the same as those of the first manufacturing method. Therefore, here, the cold rolling process will be described in detail, and the description of the other processes will be omitted.
[0090] The cold rolling step in the second manufacturing method is a cold cross rolling step in which cold rolling passes are performed in the longitudinal and transverse directions on the titanium material after the hot rolling step.
[0091] The total rolling ratio, including both the longitudinal rolling and the width rolling in this process, is 60% or more. The final rolling direction in this process is the longitudinal direction, and the direction perpendicular to the longitudinal direction is the width direction. If the total rolling ratio is 60% or more, the c-axis of the hcp is more oriented in the ND, making it possible to produce a titanium alloy thin plate with small anisotropy. The higher the rolling ratio, the closer the c-axis of the α phase of the titanium alloy thin plate is to the plate thickness direction and the greater the degree of integration, so there is no upper limit to the rolling ratio.
[0092] The cross rolling ratio is not particularly limited, and is, for example, 0.05 or more and 20.00 or less. The cross rolling ratio referred to here refers to the longitudinal rolling ratio relative to the widthwise rolling ratio (longitudinal rolling ratio / widthwise rolling ratio) applied until the plate thickness reaches the target plate thickness from 4 mm. If the cross rolling ratio is 0.05 or more and 20.00 or less, the c-axis of the hcp is more oriented in the ND, and it is possible to manufacture a thin plate with small anisotropy. In addition, it is possible to reduce the excessive band structure. The cross rolling ratio is more preferably 0.07 or more and 15.00 or less.
[0093] The rolling ratio per cold rolling pass is not particularly limited as long as the total rolling ratio is 60% or more. Here, one cold rolling pass refers to a longitudinal cold rolling or a widthwise cold rolling that is continuously performed on the hot rolled plate. Therefore, in this cold cross rolling process, when the hot rolled plate is subjected to a plurality of longitudinal cold rolling and a plurality of widthwise cold rolling, the total number of cold rolling passes is the number of cold rolling passes. For example, when the hot rolled plate is subjected to one longitudinal cold rolling and one widthwise cold rolling, the number of cold rolling passes is two. In the second manufacturing method, the longitudinal rolling or widthwise rolling may be performed a plurality of times. In addition, even if the plate thickness is 4 mm or less, reheating or the like may be performed. In addition, the widthwise hot rolling may be performed after one or several longitudinal hot rolling. Furthermore, rolling in the width direction may be carried out at any time.
[0094] The reduction ratio per cold rolling pass is not particularly limited and can be, for example, 5% or more. The reduction ratio per cold rolling pass is preferably 10% or more, more preferably 20% or more. The reduction ratio per cold rolling pass may be 80% or less, or 75% or less.
[0095] The rolling temperature in the cold cross rolling step is preferably 500°C or less. If the rolling temperature is 500°C or less, high dimensional accuracy can be obtained, and the crystal grains are refined during rolling. The rolling temperature is more preferably 400°C or less. There is no particular lower limit to the cold rolling temperature, and the cold rolling temperature can be, for example, room temperature or higher. Here, room temperature means 0°C or higher.
[0096] According to the second manufacturing method, a titanium alloy sheet is obtained in which, in the (0001) pole figure from the thickness direction, the angle between the direction showing the peak of the degree of accumulation calculated by texture analysis when the expansion index is 16 and the Gaussian half-width is 5° and the thickness direction is 35° or less, and the ratio of the 0.2% proof stress in the width direction to the 0.2% proof stress in the longitudinal direction is 0.85 to 1.10. By performing multiple rolling passes in the longitudinal direction and rolling passes in the width direction, it is possible to make the ratio of the 0.2% proof stress in the width direction to the 0.2% proof stress in the longitudinal direction close to 1.00.
[0097] In addition, when the titanium material contains a large amount of a β-phase stabilizing element such as V, hot rolling in one direction at high speed at a temperature in the β region or the α+β high temperature region where the β-phase ratio is high is likely to form a T-texture, and the anisotropy of the titanium alloy thin plate is likely to increase. However, according to the second manufacturing method, cold cross rolling is performed, so that the formation of a T-texture is suppressed even when the titanium material contains a β-phase stabilizing element such as V. As a result, it is possible to manufacture a titanium alloy plate with small anisotropy.
[0098] In addition, according to the second manufacturing method, the metal structure of the titanium alloy plate has a microstructure consisting of an equiaxed structure with an aspect ratio of 3.0 or less and a band structure with an aspect ratio of more than 3.0 and extending in the longitudinal direction, the average crystal grain size of the equiaxed structure is 0.1 μm or more and 20.0 μm or less, and the area ratio of the band structure to the area of the microstructure is 10.0% or less. This further reduces the anisotropy of the titanium alloy plate. EXAMPLES
[0099] Hereinafter, the embodiment of the present disclosure will be specifically described with reference to examples. Note that the examples shown below are merely examples of the present disclosure, and the present disclosure is not limited to the following examples.
[0100] Example 1 1. Titanium alloy plate manufacturing First, titanium alloy ingots, which are the raw material for titanium alloy plates having the chemical compositions shown in Table 1, were produced by either vacuum arc remelting (VAR), electron beam remelting (EBR), or plasma arc melting (PAM), and then titanium alloy slabs with a thickness of 150 mm, width of 800 mm, and length of 5000 mm were produced by blooming or forging. These titanium alloy slabs were then subjected to hot rolling, hot-rolled sheet annealing, shot blasting, and pickling to produce hot-rolled sheets with a thickness of 4 mm. Hot rolling is performed when the temperature of the titanium alloy slab is raised to the β transformation point T β The steel is heated to 1050 to 1100°C so that the temperature is equal to or higher than the β transformation point T β The temperature was set to 800 to 950° C. so as to satisfy the following: Elements other than those listed in Table 1 include Ti and impurities.
[0101] The chemical compositions of the hot-rolled sheets were measured for Al, Fe, Si, Ni, Cr, Mn, and V by ICP atomic emission spectrometry. O and N were measured using an oxygen and nitrogen simultaneous analyzer, inert gas fusion, thermal conductivity, and infrared absorption spectrometry. C was measured using a carbon and sulfur simultaneous analyzer by infrared absorption spectrometry. The chemical compositions of the hot-rolled sheets produced were equal to the chemical compositions of the titanium alloy slabs shown in Table 1. In addition, for titanium materials A to P shown in Table 1, phase diagrams of titanium alloys were obtained by the CALPHAD method using Thermo-Calc, an integrated thermodynamic calculation system from Thermo-Calc Software AB, and a specified database (TI3), and the β transformation points T β was calculated.
[0102] [Table 1]
[0103] Next, the obtained hot-rolled sheet was subjected to a cold rolling process under the conditions shown in Table 2. Inventive Examples 1 to 18, 30, and Comparative Example 3 in Table 2 are examples in which cold rolling with a rolling ratio of 35 to 60% per cold rolling pass and intermediate annealing under the conditions shown in Table 2 were repeated until the total rolling ratio reached 70 to 94%. Inventive Example 19 is an example in which cold rolling with a rolling ratio of 35% per cold rolling pass and intermediate annealing under the conditions shown in Table 2 were repeated until the total rolling ratio reached 60%. Inventive Example 20 is an example in which cold rolling was performed at a cold rolling temperature of 300°C. Inventive Example 21 is an example in which cold rolling with a rolling ratio of 40% per cold rolling pass and intermediate annealing under the conditions shown in Table 2 were repeated until the total rolling ratio reached 78%. The intermediate annealing step in Example 21 is an example that does not satisfy the above formula (102). Examples 22 and 23 are examples in which cold rolling was performed with a rolling reduction of 75% and 60%, respectively, without intermediate annealing. Examples 24 to 26 are examples in which cold rolling was performed with a first cold rolling pass with a rolling reduction of 75%, followed by intermediate annealing under the conditions shown in Table 2, and then cold rolling with a second cold rolling pass with a rolling reduction of 50%, resulting in a total rolling reduction of 88%. Inventive Examples 27 to 29 are examples in which the first cold rolling pass is cold rolled at a rolling reduction of 50%, the first intermediate annealing is performed under the conditions shown in Table 2, the second cold rolling pass is cold rolled at a rolling reduction of 50%, the second intermediate annealing is performed under the conditions shown in Table 2 after the second cold rolling pass, and the third cold rolling pass is cold rolled at a rolling reduction of 60%, resulting in a total rolling reduction of 90%. The reference examples are hot rolled sheets that were not subjected to the cold rolling process. Comparative Example 1 is an example in which the rolling reduction per pass is 20% and the total rolling reduction is 59%. Comparative Example 2 is an example in which the total rolling reduction is 50%. In Comparative Example 4, which used titanium material O with a high Al content, surface cracks and severe edge cracks occurred during cold rolling after hot rolling. Therefore, in Comparative Example 4, intermediate annealing and final annealing were not performed. In Table 2, "T β " is the β transformation point, and the "Larson-Miller parameter" is (T + 273.15) × (Log 10The value of (t)+20) is used. In addition, "Pattern A" in Table 2 indicates a cold rolling pattern in which the reduction ratio of the first cold rolling pass is 75%, and the reduction ratio of the second cold rolling pass is 50%. In Table 2, "Pattern B" indicates a cold rolling pattern in which the reduction ratio of the first cold rolling pass is 50%, the reduction ratio of the second cold rolling pass is 50%, and the reduction ratio of the third cold rolling pass is 60%.
[0104] [Table 2]
[0105] 2. Evaluation The titanium alloy plates according to the invention examples, reference examples and comparative examples were evaluated for the following items.
[0106] 2.1. Chemical Composition The chemical components of the titanium alloy sheets according to the invention examples, reference examples and comparative examples were measured in the same manner as in the measurement of the chemical components of the hot-rolled sheets.
[0107] 2.2. Peak location of density The observation surface of the titanium alloy plate samples according to each of the invention examples, reference examples, and comparative examples was chemically polished, and the (0001) pole figure was obtained by analyzing the crystal orientation using electron backscatter diffraction. Specifically, the L cross section was chemically polished at the center position in the width direction (TD) of each sample, and the crystal orientation analysis was performed by EBSD method on the cross section for about 2 to 10 fields of view at intervals of 1 to 2 μm in an area of (total plate thickness) × 2 mm, and the (0001) pole figure was drawn. The peak position of the concentration of a specific orientation in the (0001) pole figure was calculated by texture analysis of the inverse pole figure using the spherical harmonic function method (expansion index = 16, Gaussian half-width = 5 °) using the data of TSL Solutions' OIM Analysis software.
[0108] 2.3. Area fraction of α phase and area fraction of α phase with equivalent circle diameter of 1 μm or more The area ratio of the α phase and the area ratio of the α phase with a circle equivalent diameter of 1 μm or more were measured by the following method. The titanium alloy plate was cut perpendicular to the width direction (TD) at the center position, and a cross section was chemically polished. A region of (total plate thickness) × 200 μm on the cross section was subjected to crystal orientation analysis using the EBSD method for about 2 to 5 fields of view in steps of 1 to 5 μm. The area ratio of the α phase to the area of the above region was defined as the area ratio of the α phase. In addition, the circle equivalent diameter (area A = π × (grain size D / 2) of the α phase observed in the above field of view was calculated. 2 ) was calculated, and the total area of the α phase having an equivalent circle diameter of 1 μm or more relative to the area of the above region was defined as the area ratio of the α phase having an equivalent circle diameter of 1 μm or more. The α phase crystal grains having an equivalent circle diameter of 1 μm or more were considered to include the band structure described below.
[0109] 2.4. Aspect ratio and band structure area ratio A titanium alloy plate sample was cut perpendicular to the width direction (TD) at the center position and the cross section was chemically polished, and crystal orientation analysis was performed using the EBSD method on an area of (total plate thickness) x 200 μm of the cross section, with steps of 1 to 5 μm and 2 to 5 fields of view. From the results of this EBSD crystal orientation analysis, the aspect ratio of each crystal grain was calculated. The area ratio of crystal grains with an aspect ratio of over 3.0 was calculated as the band structure area ratio.
[0110] 2.5. Average grain size of equiaxed structure The average grain size of the equiaxed structure was calculated by calculating the circle equivalent grain size (area A = π × (grain size D / 2)2) from the grain area measured by EBSD for the equiaxed structure, and the average value based on the number of grains was used as the average grain size of the equiaxed structure.
[0111] 2.6. 0.2% proof stress The 0.2% yield strength at 25°C of each of the titanium alloy plates according to the invention examples, reference examples and comparative examples was measured in accordance with JIS Z 2241:2011.
[0112] 2.7. Average plate thickness dave The average thickness dave of the titanium alloy plate according to each invention example, reference example and comparative example was measured by the following method. For each titanium alloy plate manufactured, the thickness of each position was measured at 5 or more positions at intervals of 1 m or more in the longitudinal direction at the center position in the width direction and at the positions at 1 / 4 of the width direction from both ends of the width direction using X-ray, micrometer or caliper, and the average value of the measured thicknesses was taken as the average thickness dave.
[0113] 2.8. Plate thickness dimensional accuracy a The thickness dimensional accuracy a of the titanium alloy plate according to each invention example, reference example and comparative example is determined by using the thickness d actually measured by the above method and the average thickness dave, and calculating the maximum value of a' by the following formula (101). a'=(d-dave) / dave×100...Formula (101)
[0114] 3. Results The above evaluation results are shown in Table 3. Note that "θ" in Table 3 is the angle between the thickness direction and the direction showing the peak of the degree of integration calculated by texture analysis when the expansion index is 16 and the Gaussian half-width is 5° for an inverse pole figure using the spherical harmonic function method of electron backscatter diffraction in the (0001) pole figure from the thickness direction. Also, "θ2" in Table 3 is the angle between the width direction and the direction from the center of the pole figure showing the peak of the degree of integration calculated by texture analysis when the expansion index is 16 and the Gaussian half-width is 5° for an inverse pole figure using the spherical harmonic function method of electron backscatter diffraction in the (0001) pole figure from the thickness direction.
[0115] [Table 3]
[0116] In all of the invention examples 1 to 30, the reference examples, and the comparative examples 1 to 4, the contents of Al, Fe, Si, Ni, Cr, Mn, V, O, N and C in the produced titanium alloy plates were equal to the contents of the above elements in the hot-rolled plates used.
[0117] In the invention examples 1 to 20, the angle θ between the direction showing the peak of the density in the (0001) pole figure and the sheet thickness direction was 65° or less, and the angle θ2 between the direction showing the peak of the density and the width direction was 0°. The average crystal grain size of the equiaxed structure was 0.1 μm or more and 20.0 μm or less, and the area ratio of the band structure was 10% or less. The area ratio of the α phase was 80% or more in all cases, and the area ratio of the α phase having a circle equivalent diameter of 1 μm or more exceeded 53%. The average sheet thickness was 1.0 to 1.2 mm, and the dimensional accuracy was 0.8 to 4.5%. The longitudinal 0.2% proof stress at 25°C was 700 MPa or more, and the proof stress ratio σT / σL, which is the ratio of the longitudinal 0.2% proof stress σT at 25°C to the width direction 0.2% proof stress σL at 25°C, was 1.05 to 1.18.
[0118] In the invention example 21, the angle θ between the direction showing the peak of the density in the (0001) pole figure and the sheet thickness direction was 49°, and the angle θ2 between the direction showing the peak of the density and the width direction was 0°. The average crystal grain size of the equiaxed structure was 1.8 μm, and the area ratio of the band structure was 5.0%. The area ratio of the α phase was 88% or more, and the area ratio of the α phase having a circle equivalent diameter of 1 μm or more was 88%. The average sheet thickness was 0.9 mm, and the dimensional accuracy was 2.0%. The 0.2% proof stress at 25° C. was 805 MPa, and the proof stress ratio σT / σL was 1.12.
[0119] For Examples 22 and 23, the angle θ between the direction showing the peak of the integration degree in the (0001) pole figure and the sheet thickness direction was 50°, and the angle θ2 between the direction showing the peak of the integration degree and the width direction was 0°. The average grain size of the equiaxed structure of Example 22 was 3.5 μm, and the average grain size of the equiaxed structure of Example 23 was 10.5 μm. The area ratios of the band structure were 15.0% and 20.0%, respectively. The area ratios of the α phase were 80% or more in both cases, and the area ratios of the α phase with a circle equivalent diameter of 1 μm or more exceeded 53%. The average sheet thicknesses were 1.0 mm and 1.6 mm, and the dimensional accuracy was 2.0% and 2.5%. The 0.2% proof stress at 25° C. was 700 MPa or more, and the proof stress ratios σT / σL were 1.11 and 1.15.
[0120] In the invention examples 24 to 26, the angle θ between the direction showing the peak of the density in the (0001) pole figure and the sheet thickness direction was 65° or less, and the angle θ2 between the direction showing the peak of the density and the width direction was 0°. The average grain size of the equiaxed structure was 0.1 μm or more and 20.0 μm or less, and the area ratio of the band structure was 10% or less. The area ratio of the α phase was 80% or more in all cases, and the area ratio of the α phase having a circle equivalent diameter of 1 μm or more exceeded 53%. The average sheet thickness was 0.5 mm in all cases, and the dimensional accuracy was 1.0 in all cases. The longitudinal 0.2% proof stress at 25° C. was 700 MPa or more, and the proof stress ratio σT / σL was 1.05 or more and 1.18 or less.
[0121] In the invention examples 27 to 29, the angle θ between the direction showing the peak of the integration degree in the (0001) pole figure and the sheet thickness direction was 65° or less, and the angle θ2 between the direction showing the peak of the integration degree and the width direction was 0°. The average crystal grain size of the equiaxed structure was 0.1 μm or more and 20.0 μm or less, and the area ratio of the band structure was 10% or less. The area ratio of the α phase was 80% or more in all cases, and the area ratio of the α phase having a circle equivalent diameter of 1 μm or more exceeded 53%. The average sheet thickness was 0.4 mm in all cases, and the dimensional accuracy was 1.0% or less in all cases. The longitudinal 0.2% proof stress was 700 MPa or more, and the proof stress ratio σT / σL was 1.05 to 1.18.
[0122] For Example 30, the angle θ between the direction showing the peak of the integration degree in the (0001) pole figure and the sheet thickness direction was 45°, and the angle θ2 between the direction showing the peak of the integration degree and the width direction was 0°. The average crystal grain size of the equiaxed structure was 3.5 μm, and the area ratio of the band structure was 5.0%. The area ratio of the α phase was 85% or more, and the area ratio of the α phase having a circle equivalent diameter of 1 μm or more was 80%. The average sheet thickness was 1.0 mm, and the dimensional accuracy was 1.5%. The 0.2% proof stress was 800 MPa, and the proof stress ratio σT / σL was 1.14.
[0123] In the reference example, the angle θ between the direction showing the peak of the density in the (0001) pole figure and the sheet thickness direction was more than 65°. Therefore, the yield strength ratio σT / σL was more than 1.18, indicating strong anisotropy.
[0124] In addition, in Comparative Example 1, the rolling ratio per run was as small as 20%, and the total rolling ratio was also as small as 59%. Therefore, the angle θ between the direction showing the peak of the density in the (0001) pole figure and the sheet thickness direction was more than 65°. Therefore, the yield strength ratio σT / σL was more than 1.18, indicating strong anisotropy. In Comparative Example 2, the rolling ratio per run was 50%, but intermediate annealing and cold rolling were not repeated, and the total rolling ratio was small at 50%. Therefore, the angle θ between the direction showing the peak of the density in the (0001) pole figure and the sheet thickness direction was more than 65°. Therefore, the yield strength ratio σT / σL was more than 1.18, indicating strong anisotropy. In Comparative Example 3, the Al content was low, so the 0.2% yield strength was as small as 598 MPa. In Comparative Example 4, as described above, surface cracks and severe edge cracks occurred during cold rolling.
[0125] Example 2 In the same manner as in Example 1, hot-rolled sheets having the chemical compositions shown in A, B, C, E, and M in Table 1 and a thickness of 4 mm were produced.
[0126] Next, the obtained hot-rolled sheet was subjected to a cold rolling process under the conditions shown in Table 4. Inventive Examples 31 to 37 in Table 2, multiple cold rolling passes were performed so that the rolling ratio per cold rolling pass was 5% or more and the total rolling ratio was the total rolling ratio shown in Table 4. Inventive Examples 31 to 35 in Table 4 are examples in which multiple cold rolling passes at a rolling temperature of 25°C and intermediate annealing under the conditions shown in Table 2 were repeated, and cold cross rolling was performed until the total rolling ratio was 60 to 75%. Intermediate annealing was performed at a temperature of 680 to 900°C for 60 to 28800s, and final annealing was performed at a temperature of 650 to 930°C for 120 to 28800s. The cross rolling ratio of Inventive Examples 32 to 36 was 0.4 to 7.0. Inventive Example 36, multiple cold rolling passes at a rolling temperature of 400°C and intermediate annealing under the conditions shown in Table 4 were repeated, and cold cross rolling was performed until the total rolling reduction was 75%. Intermediate annealing was performed at a temperature of 800°C for 120 seconds, and final annealing was performed at a temperature of 850°C for 120 seconds. The cross rolling ratio of Inventive Example 36 was 13.0. Inventive Example 37, multiple cold rolling passes at a rolling temperature of 25°C and intermediate annealing under the conditions shown in Table 4 were repeated, and cold cross rolling was performed until the total rolling reduction was 62%. Intermediate annealing was performed at a temperature of 800°C for 120 seconds, and final annealing was performed at a temperature of 850°C for 120 seconds. The cross rolling ratio of Inventive Example 37 was 0.17. At this time, the rolling in the cross direction was performed while appropriately cutting according to the width of the rolling roll so as to obtain a size that can be rolled.
[0127] [Table 4]
[0128] For the titanium alloy plates according to each of the invention examples, the same items as those in Example 1 were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 5.
[0129] [Table 5]
[0130] In the invention examples 31 to 37, the angle θ between the direction showing the peak of the accumulation degree in the (0001) pole figure and the sheet thickness direction was 35° or less. The average crystal grain size of the equiaxed structure was 0.1 μm or more and 10.0 μm or less, and the area ratio of the band structure was 10% or less. The area ratio of the α phase was 80% or more in all cases, and the area ratio of the α phase having a circle equivalent diameter of 1 μm or more exceeded 53%. The average sheet thickness was 1.0 to 1.8 mm, and the dimensional accuracy was 1.5 to 3.5% or less. The 0.2% proof stress at 25°C was 700 MPa or more, and the proof stress ratio σT / σL, which is the ratio of the 0.2% proof stress σT in the width direction at 25°C to the 0.2% proof stress σL in the longitudinal direction at 25°C, was 0.85 to 1.10.
[0131] Although the preferred embodiment of the present disclosure has been described in detail above, the present disclosure is not limited to such examples. It is clear that a person having ordinary knowledge in the technical field to which the present disclosure belongs can conceive of various modified or amended examples within the scope of the technical ideas described in the claims, and it is understood that these also naturally belong to the technical scope of the present disclosure.
Claims
1. In mass percent, Al: more than 4.0%, less than 6.6%, Fe: 0% or more, 2.3% or less, V: 0% or more, 4.5% or less, Si: 0% or more, 0.60% or less, C: 0% or more and less than 0.080%; N: 0% or more, 0.050% or less, O: 0% or more, 0.40% or less, Ni: 0% or more and less than 0.15% Cr: 0% or more and less than 0.25%; and Mn: 0% or more and less than 0.25% with the remainder being Ti and impurities, The area ratio of the α phase is 80% or more, The area ratio of α phase having an equivalent circle diameter of 1 μm or more is more than 53%, In a (0001) pole figure from the thickness direction, an inverse pole figure using the spherical harmonic function method of electron backscatter diffraction has an expansion index of 16, and the angle between the direction showing the peak of the accumulation degree calculated by texture analysis when the Gaussian half width is 5° and the thickness direction is 65° or less; A titanium alloy plate having an average plate thickness of 2.5 mm or less.
2. The microstructure is composed of an equiaxed structure having an aspect ratio of 3.0 or less and a band structure having an aspect ratio of more than 3.0 and extending in the longitudinal direction; The average grain size of the equiaxed structure is 0.5 μm or more and 20.0 μm or less, The titanium alloy plate according to claim 1, wherein the area ratio of the band structure to the area of the microstructure is 10.0% or less.
3. In mass%, Fe: 0.5% or more and 2.3% or less, or V: 2.5% or more and 4.5% or less; The titanium alloy plate according to claim 1 or 2, comprising:
4. In place of a portion of the Fe or V, Ni: less than 0.15% Cr: less than 0.25%; and The titanium alloy plate according to claim 3, containing one or more selected from the group consisting of: Mn: less than 0.25%.
5. The titanium alloy plate according to any one of claims 1 to 4, wherein the smaller one of the 0.2% proof stress in the longitudinal direction at 25 ° C. or the 0.2% proof stress in the width direction at 25 ° C. is 700 MPa or more and 1200 MPa or less.
6. In a (0001) pole figure from the plate thickness direction, an inverse pole figure obtained by using the spherical harmonic function method of electron backscatter diffraction has an expansion index of 16 and a Gaussian half-width of 5°, and the angle between the direction showing the peak of the accumulation degree calculated by texture analysis and the width direction is 10° or less; The titanium alloy plate according to any one of claims 1 to 5, wherein the ratio of the 0.2% proof stress in the width direction to the 0.2% proof stress in the longitudinal direction is 1.05 or more and 1.18 or less.
7. In the (0001) pole figure from the thickness direction, the inverse pole figure using the spherical harmonic function method of electron backscatter diffraction has an expansion index of 16, and the angle between the thickness direction and the direction showing the peak of the accumulation degree calculated by texture analysis when the Gaussian half width is 5° is 35° or less. The titanium alloy plate according to any one of claims 1 to 5, wherein the ratio of the 0.2% proof stress in the width direction to the 0.2% proof stress in the longitudinal direction is 0.85 or more and 1.10 or less.
8. The titanium alloy plate according to any one of claims 1 to 7, wherein the dimensional accuracy of the plate thickness is 5.0% or less with respect to the average plate thickness.
9. In mass percent, Al: more than 4.0%, less than 6.6%, Fe: 0% or more, 2.3% or less, V: 0% or more, 4.5% or less, Si: 0% or more, 0.60% or less, C: 0% or more and less than 0.080%; N: 0% or more, 0.050% or less, O: 0% or more, 0.40% or less, Ni: 0% or more and less than 0.15% Cr: 0% or more and less than 0.25%; and Mn: 0% or more and less than 0.25% with the remainder being Ti and impurities, The area ratio of the α phase is 80% or more, The area ratio of α phase having an equivalent circle diameter of 1 μm or more is more than 53%, In a (0001) pole figure from the thickness direction, an inverse pole figure using the spherical harmonic function method of electron backscatter diffraction has an expansion index of 16, and the angle between the direction showing the peak of the accumulation degree calculated by texture analysis when the Gaussian half width is 5° and the thickness direction is 65° or less; A titanium alloy coil having an average thickness of 2.5 mm or less.
10. A method for producing a titanium alloy plate according to any one of claims 1 to 8, a cold rolling process of performing one or more cold rolling passes in the longitudinal direction of a titanium material containing, by mass%, Al: more than 4.0% and 6.6% or less, Fe: 0% or more and 2.3% or less, V: 0% or more and 4.5% or less, Si: 0% or more and less than 0.60%, C: 0% or more and less than 0.080%, N: 0% or more and 0.050% or less, O: 0% or more and 0.40% or less, Ni: 0% or more and less than 0.15%, Cr: 0% or more and less than 0.25%, and Mn: 0% or more and less than 0.25%, with the balance being Ti and impurities; and a final annealing step of annealing the titanium material after the last cold rolling pass, A method for producing a titanium alloy plate, wherein the cold rolling step has a rolling ratio per cold rolling pass of more than 30% and a total rolling ratio of 60% or more.
11. When the cold rolling process is performed in a plurality of cold rolling passes, the cold rolling process includes an intermediate annealing process in which the titanium material is annealed between the plurality of cold rolling passes, and the annealing conditions of the intermediate annealing process and the final annealing process are an annealing temperature of 600° C. or more (T β -50) ℃ or less, and the annealing temperature T (℃) and the holding time t (seconds) at the annealing temperature satisfy the following formula (1). 22000≦(T+273.15)×(Log 10 (t) + 20) ≦ 27000 … Formula (1) Here, T β is the β transformation point (°C).
12. A method for producing a titanium alloy plate according to any one of claims 1 to 8, a cold cross rolling process in which cold rolling passes are performed in the longitudinal and transverse directions of the titanium material, the titanium material containing, by mass%, Al: more than 4.0% and not more than 6.6%, Fe: 0% or more and not more than 2.3%, V: 0% or more and not more than 4.5%, Si: 0% or more and not more than 0.60%, C: 0% or more and less than 0.080%, N: 0% or more and not more than 0.050%, O: 0% or more and not more than 0.40%, Ni: 0% or more and less than 0.15%, Cr: 0% or more and less than 0.25%, and Mn: 0% or more and less than 0.25%, with the balance being Ti and impurities; A final annealing step of annealing the titanium material after the cold cross rolling step, The total rolling ratio in the cold cross rolling step is 60% or more, A method for producing a titanium alloy plate, wherein a cross rolling ratio, which is a ratio of the rolling ratio in the longitudinal direction to the rolling ratio in the width direction, is 0.05 or more and 20.00 or less.
13. When the cold cross rolling process is performed using a plurality of cold rolling passes, the cold cross rolling process includes an intermediate annealing process for annealing the titanium material between the plurality of cold rolling passes, and the annealing conditions for the intermediate annealing process and the final annealing process are an annealing temperature of 600° C. or higher (T β -50) ℃ or less, and the annealing temperature T (℃) and the holding time t (seconds) at the annealing temperature satisfy the following formula (1). 22000≦(T+273.15)×(Log 10 (t) + 20) ≦ 27000 … Formula (1) Here, T β is the β transformation point (°C).
14. A method for producing a titanium alloy coil according to claim 9, a cold rolling process of performing one or more cold rolling passes in the longitudinal direction of a titanium material containing, by mass%, Al: more than 4.0% and not more than 6.6%, Fe: 0% or more and not more than 2.3%, V: 0% or more and not more than 4.5%, Si: 0% or more and not more than 0.60%, C: 0% or more and less than 0.080%, N: 0% or more and not more than 0.050%, O: 0% or more and not more than 0.40%, Ni: 0% or more and less than 0.15%, Cr: 0% or more and less than 0.25%, and Mn: 0% or more and less than 0.25%, with the balance being Ti and impurities; and a final annealing step of annealing the titanium material after the last cold rolling pass, A method for producing a titanium alloy coil, wherein the cold rolling step has a rolling ratio per cold rolling pass of more than 30% and a total rolling ratio of 60% or more.
Citation Information
Patent Citations
Low-cost medium-high-strength corrosion-resistant titanium alloy and processing method thereof
CN104152744A
Production of cold rolled titanium alloy plate
JP1986147864A
Manufacture of alpha+beta-type titanium alloy sheet
JP1987033750A
Manufacture of alpha+beta type titanium alloy cold rolled plate
JP1989127653A
Alpha+Beta type titanium alloy
JP1995062474A